2017
DOI: 10.1055/s-0037-1605584
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Early Hip Osteoarthritis: Ultrasound-Guided Platelet Rich Plasma versus Hyaluronic Acid Injections in a Randomized Clinical Trial

Abstract: Purpose  The aim of this study was to compare the clinical efficacy of ultrasound-guided intra-articular injections of autologous platelet rich plasma (PRP) versus hyaluronic acid (HA) for symptomatic early osteoarthritis (OA) of the hip. Methods  A prospective controlled double-blinded randomized trial on 80 patients with hip OA was conducted. The patients were divided in two groups of 40 patients each: group 1 underwent three PRP intra-articular ultrasound-guided injections, whereas group 2 underwent three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 21 publications
0
66
0
Order By: Relevance
“…Thus, PRP is emerging as a novel treatment for musculoskeletal pathologies, such as ligament injury, muscle tears, tendinopathies, and osteoarthritis [5,6]. For instance, intra-articular injections of autologous PRP are effective in patients with moderate osteoarthritis [7]. In previous studies, we showed that PRP accelerated bone union and induced a reduction of the bone union period in both rats and humans with spinal posterolateral fusion (PLF) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PRP is emerging as a novel treatment for musculoskeletal pathologies, such as ligament injury, muscle tears, tendinopathies, and osteoarthritis [5,6]. For instance, intra-articular injections of autologous PRP are effective in patients with moderate osteoarthritis [7]. In previous studies, we showed that PRP accelerated bone union and induced a reduction of the bone union period in both rats and humans with spinal posterolateral fusion (PLF) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…3,13,41 Two studies used 10% calcium chloride, 3,13 and 1 study used an undisclosed exogenous activator. 41 Three studies 14,15,29 (42.9%) did not mention whether an activator was used, and 1 study 42 (14.3%) specifically reported not using an activator. Detailed PRP preparation information is reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Both the HHS and the modified HHS have been used extensively in clinical trials involving hip pathology and treatment of different hip conditions. The HHS has been used in trials that range from assessment of treatment choice for femoral neck and intertrochanteric femur fractures to assessment of effectiveness of different injections for osteoarthritis of the hip . The HHS is also a popular tool in studies relating to THAs given the focus of the measure on pain and impaired physical function, which are the main indications for a THA .…”
Section: Harris Hip Scorementioning
confidence: 99%